Highly Regio- and Stereoselective Hydrogermylation of Fluorinated Alkyl Propiolate - Kawtharani, Ranin.; Elmasri, Mirvat; Cherry, Khalil; Jacquemin, Johan; Abarbri, Mohamed (SynOpen, 2019)
The selective introduction of fluoroalkylated vinylmetals in controlled strategies is a challenging process for many chemists. This study reports the highly regio- and stereoselective synthesis of functionalized vinylgermanes bearing a perfluoroalkyl group from perfluoroalkylated acetylenic esters via AlCl3-catalyzed hydrogermylation. Regio- and stereoselectivity are highly dependent on the nature of the catalyst and the nature of the fluoroalkyl group of alkyne.
Keywords: regio- and stereoselective hydrogermylation; fluorinated ethyl propiolate; AlCl3; triphenyl- and tributylgermanes; fluorinated vinylgermanes